Using Schools of Nursing to Help Fill the Gap - Resha, Cheryl (NASN School Nurse, 2016)
The shortage of school nurses, school nurses covering multiple buildings, and the expanded role of the school nurse has called for innovative ideas to meet the growing health care needs of youth. Partnering with local schools of nursing may be a welcomed strategy. This brief article will share the benefits of hosting student nurses as well as identify ways to begin these partnerships. © 2016 The Author(s).
Keywords: Adult; Curriculum; Education, Nursing, Baccalaureate; Female; Humans; Interprofessional Relations; Male; Middle Aged; Organizational Innovation; School Health Services; School Nursing; Schools, Nursing; Students, Nursing; United States; adult; curriculum; dept.nur; education; female; health promotion; human; male; middle aged; nursing education; nursing student; organization; organization and management; partnerships; public relations; school health nursing; school health service; schools of nursing; student nurses

Enhancing student nurse learning through participation in a community-based educational program for children and families - Krol, Maria; Resha, Cheryl; Glendon, Mary Ann (Journal of Community Health Nursing, 2016)
Health disparities, especially among minorities, persist; obesity is a national concern; and the combined effect can be significant for families and populations. In an effort to address obesity at an early age, the National Association of Hispanic Nurses (NAHN), developed the Muevete USA project. Muevete USA (from the Spanish verb for to move) features five lesson plans on healthy lifestyles for children and their families. This article describes Muevete USA, the partnership with a local school of nursing, the implementation of the program at the local level and the emerging program and student outcomes of a successful partnership.
Keywords: Child; Child Health; Community-Based Participatory Research; Humans; Obesity; Schools; Students, Nursing; child; child health; dept.nur; human; nursing student; obesity; participatory research; school